תשובה:
# dy / dx = (x - 2 + 2x + 1) / (x ^ 2 + 1) (x-1)) #
הסבר:
# y = ln (x-1) / (x ^ 2 + 1)) #
# y = ln (x-1) -ln (x ^ 2 + 1) #
השתמש בכלים של הלוגריתמים
עכשיו להבדיל
# d / dx = 1 (x-1) -1 / (x ^ 2 + 1) * d / dx (x ^ 2 + 1) #השתמש כלל שרשרת
# dy / dx = 1 / (x-1) -1 / (x ^ 2 + 1) * 2x #
# dy / dx = 1 / (x-1) - (2x) / (x ^ 2 + 1) # קח את LCD כמו ((x-1) (x ^ 2 + 1)
# (/ dx =) (x + 2 + 1) /) (x ^ 2 + 1) (x-1) (x-1)) - (2x) (x-1)) / (x ^ 2 + 1) x-1))) #
# dy / dx = (x ^ 2 + 1-2x ^ 2 + 2x) / ((x ^ 2 + 1) (x-1) #
# dy / dx = (x - 2 + 2x + 1) / (x ^ 2 + 1) (x-1)) #